Black hole information loss issue and the global hyperbolicity of spacetimes - Pêgas, Juan Vitor Oliveira [UNESP] (2025)
In the absence of a quantum theory of gravity, quantum field theory in curved spacetimes provides the most solid framework to study the interplay between gravity and quantum mechanics. One of the most striking consequences of this theory is the Hawking effect. In this scenario, the fade of black holes is its complete evaporation due to the emission of thermal radiation. As a consequence, a pure state of a quantum field prepared in the asymptotic past that collapses in a black hole will evolve into a mixed state in the asymptotic future, violating unitarity. This is the so-called ``black hole information loss paradox''. In this dissertation, we argue that, far from paradoxical, the information loss is a prediction of quantum field theory in curved spacetimes and not a violation. In addition, we address the problem of how to conciliate the unitary evolution of a quantum field and the Hawking effect without relying on a specific quantum gravity model.